Clases virtuales y su impacto en el desarrollo académico del 8º año de educación básica de la Unidad Educativa Los Guayacanes del cantón Quevedo Provincia de Los Ríos 2022 - Piguave Carrera, Janina Johanna (2022)
In the present investigation, it deals with virtual classes and their impact on the school development of students due to the Covid-19 pandemic. I force educational institutions to stop face-to-face classes, facing a different experience in their school activities, adapting to multiple changes in order to continue their learning. In such a way that the lack of knowledge towards the use of technological tools caused a great impact in a negative way for the eighth-year students and teachers of the Los Guayacanes Educational Unit. Finally, the teachers looked for new methods in which the schedule and the pedagogical tools used by them were altered, making the development of Virtual Learning Environments essential. The objective of this document is to analyze the impact of virtual learning in times of pandemic; It is exposed to know the different realities of the educational community through the study of data on school irregularities, internet connectivity, among others. It is descriptive in nature, it specifies the educational-social aspects that occurred in virtual environments during the health emergency. For the collection of information, it was carried out through the bibliographic-documentary search supported from the direct observation-experience of the social content. A survey was also started and applied through a google form, taking into account the teaching staff and students of said institution.